An evaluation of properties of four heat treated wood species - Kesik, Haci Ismail; Korkut, Suleyman; Hiziroglu, Salim; Sevik, Hakan (Elsevier BV, 2014)
Abstract The objective of this work was to investigate the effect of heat treatment on swelling, hardness, and surface quality of four wood species, namely black locust (Robinia pseudoacacia L.), common alder (Alnus glutinosa L.), Western prickly juniper (Juniperus oxycedrus L.) and plum (Prunus domestica L.). Samples were exposed to temperature levels of 130 and 160 °C for 3 and 7 h. Surface quality and hardness of the specimens were determined using a stylus technique and Janka hardness, respectively. Based on the findings in this work overall dimensional stability of all four species improved with heat treatment. Surface quality of the samples was also enhanced due to heat exposure. Scanning electron micrographs revealed that some distortion and cell modification took place as a result of heat treatment. Furthermore, hardness of the samples was adversely influenced by the heat exposure. It appears that the properties of all samples exposed to a temperature of 160 °C for 7 h were more pronounced than those treated with a temperature of 130 °C for 3 h.
Keywords: Black locust; Plum; Western prickly juniper; Heat treatment; Common alder; 4. Education; 15. Life on land